A memória na ficção de Francisco Dantas : cenas da narrativa e do narrador pós-moderno - Andrade, Maria Luzia Oliveira (2010)
This dissertation investigates the implications of memory in fiction Francisco J. C. Dantas, in the context of a postmodern scene still under construction. Coivara da memória (1991), Cartilha do silêncio (1997) and Sob o peso das sombras (2004) are literary texts in which the sophistication of language and the fragmented narrative narrators put into play direct and indirect memories. With that, the aim is to understand how, in these fictional texts, the memory is constructed and represented, starting from ruins or fragments, how that remembering reflects and metaphor the tradition. Although our arguments happen in a gradual process, in which one chapter offers clues to the subsequent chapter, the work is presented in three steps. The first concerns the representation of social memory by giving voice to time and individual experiences on the sidelines of a social process and a family clan. The second corresponds to the fragmentation of narrative and the subsequent deceiving reading that the narrators present to the reader. The third is dedicated to the critical appropriation of tradition by Dantas, the consequent intertextual dialogue with it, which results in the weight of tradition itself and the potentiation of characters in a condition to the social margin. The weight of memory, the fragmentation of narrative and tradition as a loan in the postmodern scene form the foundation of this work that analyzes such elements in a past-present cycle, while use of different social voices and some procedures in the ways of recounting the memories.